ReFEx launch with a sounding rocket - a challenging mission on a reliable carrier - Schmidt, Alexander; Kirchhartz, Rainer; Hörschgen-Eggers, Marcus; Kallenbach, Alexander (2019)
Sounding rockets are a platform eminently suited for conducting experiments with supersonic and hypersonic experimental vehicles. For many years, but especially during the last decade, DLR's Mobile Rocket Base MORABA took part as a launch provider in a variety of missions dedicated to hypersonic and reentry vehicle research. This included missions for cooperation partners, like the HIFiRE program and the ScramSpace project. These were launched from Andøya Space Center, Norway, as well as Woomera in Australia. DLR's research and technology program also relies on sounding rockets as carrier vehicles to conduct aerothermodynamic research. The ROTEX-T mission (measurements of loads due to heat and air resistance) as well as SHEFEX I and SHEFEX II (hypersonic reentry experiments) made a significant contribution to hypersonic research in general and demonstrated the applicability of sounding rockets to the research field. Especially SHEFEX II had to master some challenges, like a precession maneuver with a spinning rocket to achieve the required initial conditions for the scientific flight path. For the ReFEx flight, which is planned to fly in Woomera 2021, MORABA's VSB-30 vehicle was chosen. This vehicle has been launched successfully for more than 30 flights to date and is therefore considered as a reliable vehicle. It also served as a carrier vehicle for some of the above mentioned missions. Consequently, ReFEx as a hypersonic research mission launched on a sounding rocket by MORABA as a propulsion system is a logical choice. This paper gives an overview on MORABA's activities in the above mentioned programs and an outlook towards the additional challenges the ReFEx mission might face.